A successful symposium of “Multi-origin of soft-sediment deformation structures and seismites” - Zeng-Zhao Feng (Journal of Palaeogeography, 2017)
A great progress has been made in researches of soft-sediment deformation structures (SSDS) and seismites in China. However, the research thought was not open-minded. About the origin of SSDS, it was almost with one viewpoint, i.e., almost all papers published in journals of China considered the beds with SSDS as seismites. It is not a good phenomenon. In order to change this phenomenon, in early 2016, Feng et al. wrote a paper “Researches of soft-sediment deformation structures and seismites in China — A brief review” as “to cast a brick to attract the jade”, emailed this paper to many geologists in China and other countries, and invited them to write papers for the symposium of “Multi-origin of soft-sediment deformation structures and seismites”. “The seismite problem” by Prof. G. Shanmugam is the first paper that we have received. The symposium was successfully held in September 24, 2016 at Henan Polytechnic University, Jiaozuo, Henan Province, China. The products of this symposium are as follows: (1) The terms “SSDS” and “Multi-origin of SSDS” were accepted by numerous geologists. (2) The definition of seismites by Seilacher (1969), i.e., “fault-graded beds interpreted as seismites”, should be obsoleted, however, the definition by many geologists today, i.e., “the seismites are the beds with SSDS really induced by earthquakes”, should not be obsoleted and should be retained. (3) The term “seismites” should be strictly restricted to the beds with SSDS that are really induced by earthquakes. (4) The clastic injections are also with multi-origin, and they cannot definitely be the seismites and may not be the exact criteria of in-situ earthquakes. (5) The most important product of this symposium is that the phenomenon of almost one viewpoint of the researches of SSDS and seismites in China has been Changed eventually.